Laura Corradi - Gypsy Feminism: Intersectional Politics, Alliances, Gender and Queer Activism: New York, NY: Routledge/Taylor & Francis Group, 2018, 93 s., ISBN: 978-1-138-30033-0 - Ort, Jan (Romano džaniben, 2017)
RECENZE